Numerical analysis on the effect of building spacing and podium on the flow structure over high rise residential buildings / A. A. Rahman ... [et al.] - Rahman, A. A.; Mohamad, M.F.; Jaffar, A.; Razak, A.A.; N., Ikegaya (Smart Manufacturing Research Institute (SMRI), 2024)
Urban environments with high-rise buildings often experience intensified wind speeds at the pedestrian level, which can compromise comfort and safety. The growing demand for urban housing has led to the proliferation of such buildings, but the impact of building geometry and configuration on local wind conditions remains underexplored, particularly concerning the presence of podium structures. This study addresses the critical issue of pedestrian-level wind (PLW) by investigating how the spacing between buildings and the inclusion of podiums affect wind dynamics. Using computational fluid dynamics (CFD) simulations, the study models wind flow around two high-rise residential buildings arranged back-to-back under different spacing configurations (0.16H, 0.31H, and 0.63H) with and without podiums. The primary objective is to assess wind speed ratios and vortex formations to identify optimal design configurations for enhancing pedestrian comfort and safety. The results show that building spacing of 0.31H without podiums yields the lowest wind speed ratio at the pedestrian level, enhancing safety. The introduction of a podium significantly alters wind flow patterns, particularly by increasing downwash flow and generating larger vortices above the podium level, which can exacerbate wind speeds at higher elevations. These findings underscore the importance of careful urban design considerations, particularly regarding building spacing and podium integration, to mitigate adverse wind effects. The study provides actionable insights for architects and urban planners to create wind-sensitive designs that improve the quality of life in densely built environments.